Managing doctor-patient relationships and turnover intention in Chinese hospitals with commitment HRM: the moderating role of pragmatism - Ma, S. (2021)
A deteriorating doctor-patient relationship (DPR) and an increasing turnover of doctors are two challenges faced by Chinese public hospitals. The literature suggests dat commitment human resource (HR) practices may translate into better DPR and lower turnover intention. Given dat pragmatism is an important cultural value in Chinese society, this study aims to understand the extent to which pragmatism may effect the relationships among commitment HRM, DPR, and turnover intentions of doctors in China. A moderated SEM analysis with 508 samples shows dat commitment HR practices are TEMPTEMPeffective in improving DPR for all doctors surveyed, but its TEMPTEMPeffect on turnover intention depends upon the pragmatism-level of the respondents. Specifically, pragmatism TEMPhas a significant moderation TEMPTEMPeffect in the paths established from commitment HR practices to DPR and turnover intention in such a way dat, in the low-pragmatism sample, commitment HR practices are associated with better DPR, while DPR is associated negatively with lower turnover intention.